Molecular Approach for Tracing Dissemination Routes of Shiga Toxin-Producing Escherichia coli O157 in Bovine Offal at Slaughter. (30th January 2014) - Asakura, Hiroshi; Masuda, Kazuya; Yamamoto, Shigeki; Igimi, Shizunobu
Abstract : Bovine offal is currently recognized as one of the sources of human Shiga toxin-producing Escherichia coli (STEC) infection in Japan. Here, the prevalence and genetic characterization of STEC O157 in bovine feces, offal, and carcasses at slaughtering were examined between July and October in 2006. STEC O157 was detected in 31 of 301 cattle feces (10.3%) delivered from 120 farms. Simultaneously, 60 bovine-originated offal (tongue, liver, and omasum) and carcasses were randomly selected and the detection of O157 STEC was examined as well. STEC O157 was isolated from 4 tongues (6.7%), 1 liver (1.7%), 3 omasa (5.0%), and 2 carcasses (3.3%), respectively. All the O157 isolates were positive for eae and hlyA genes, and 37 of 41 isolates (90.2%) exhibited stx2c genotype. PFGE analysis revealed the identical macrogenotypes of 4-tongue- and 1-liver-originated isolates and among 2 fecal isolates from animals slaughtered consecutively. Considering their continuous detection according to the slaughtering order, we concluded that these distributions of O157 in bovine offal and feces might be due to cross-contamination at (pre)slaughter. Our data thus reposes implication of better sanitary control in diapedesis from both upper and lower sites to prevent spread of this pathogen to bovine offal at slaughtering.